RELATIONSHIP OF LABELINGHEALTH WARNING AND SMOKING RISK PERCEPTION WITH CIGARETTE CONSUMPTION (IN PONTIANAK CITY) - RAHIM RAHIM; DEWI KURNIATI; IMELDA IMELDA (Fakultas Pertanian Universitas Tanjungpura, 2019)
The number of smokers in Indonesia every year increases, various kinds of efforts that have been done by the government to reduce the number of smokers that exist but there is no awareness of the people who consume cigarettes. Cigarettes are a different health challenge compared to viruses and bacteria that humans can avoid, cigarettes actually become the needs of consumers. The purpose of this study was to analyze the relationship between cigarette warning labeling and the risk perception of smoking with cigarette consumption on 96 respondents by non-probability sampling with descriptive methods using correlation spearman rank (rho) analysis. The results showed that warning labeling and risk perception of smoking had a significant effect on cigarette consumption. The effort that must be done by the government is to increase labeling, increase the type of spooky image design and clarify the words listed on the cigarette packaging, and the community must be better at perceiving the dangers of smoking. Keywords :Labeling, Risk Perception, Cigarette Consumption, Correlation Spearman Rank (rho)